A Novel Method for Rotor Field-Oriented Control of Single-Phase Induction Motor - M. Jannati; T. Sutikno; N. R. N. Idris; M. J. A. Aziz (International Journal of Electrical and Computer Engineering (IJECE), 2015)
This paper presents a novel rotor field-oriented control (RFOC) method for asymmetrical single-phase induction motor (SPIM). It is shown in this paper that by using a suitable transformation matrix (TM) for stator current variables, the asymmetrical equations of SPIM are transformed into symmetrical equations. Based on this similarity, a novel vector conrol technique for SPIM is presented. Performance of the proposed method is assessed using MATLAB/SIMULINK software. Simulation results showed the excellence speed and torque responses obtained using the proposed technique.